Large Scale Genome Analysis Shows that the Epitopes for Broadly Cross-Reactive Antibodies Are Predominant in the Pandemic 2009 Influenza Virus A H1N1 Strain - Edgar E. Lara-Ramírez (Viruses, 2013)
The past pandemic strain H1N1 (A (H1N1)pdm09) has now become a common component of current seasonal influenza viruses. It has changed the pre-existing immunity of the human population to succeeding infections. In the present study, a total of 14,210 distinct sequences downloaded from National Center for Biotechnology Information (NCBI) database were used for the analysis. The epitope compositions in A (H1N1)pdm09, classic seasonal strains, swine strains as well as highly virulent avian strain H5N1, identified with the aid of the Immune Epitope DataBase (IEDB), were compared at genomic level. The result showed that A (H1N1) pdm09 contains the 90% of B-cell epitopes for broadly cross-reactive antibodies (EBCA), which is in consonance with the recent reports on the experimental identification of new epitopes or antibodies for this virus and the binding tests with influenza virus protein HA of different subtypes. Our analysis supports that high proportional EBCA depends on the epitope pattern of A (H1N1)pdm09 virus. This study may be helpful for better understanding of A (H1N1)pdm09 and the production of new influenza vaccines.